'Der König rief, und alle, alle kamen' Jewish military chaplains on duty in the Austro-Hungarian army during World War I. Issue 3 (1st September 2016) - Hecht, Dieter J.
Abstract: The compulsory conscription of Jews was introduced in the Habsburg Monarchy in 1788. In 1866, the first Jewish military chaplain was appointed. Until World War I, only a few rabbis served in the army, but they had a significant impact on the self-assertion of Jewish soldiers in the Habsburg armed forces. Between 1914 and 1918, the number of Jewish military chaplains rose to 133, almost three times higher than in the German army. Some of the rabbis still held prestigious positions after World War I, but most disappeared into oblivion. This paper assesses and reconstructs the lives and efforts of these military rabbis, placing a special focus on the Jewish military chaplaincy in Vienna and its head, Arnold Frankfurter.